Successful clinical outcome in complicated monochorionic twins: case series - Singh, Anil K.; Malhotra, Gunjan; Mohana Priya, N.; Tangri, Manoj K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Monochorionic twins have some unique complications like twin-to-twin transfusion syndrome (TTTS), twin anemia polycythemia sequence (TAPS), twin reverse arterial perfusion syndrome (TRAP) and conjoined twins which are otherwise not seen in dichorionic twins. In this case series, we report 3 cases of monochorionic twins who had complications. Our first case had monochorionic twin with a pump fetus and a TRAP. The second case had TTTS stage I and after spontaneous preterm premature rupture of membranes at 32 weeks, delivered both fetuses vaginally at an interval of about 3 hours. Our third case had TTTS stage II and she underwent selective fetoscopic laser photocoagulation of intertwin anastomotic vessels at about 25 weeks and subsequently multiple episodes of amnioreduction till 31 weeks when she underwent emergency caesarean delivery. Our study highlights the need for constant vigilance in patients with monochorionic twins to look for complications like TTTS and TRAP.